The Effect of Stellar Magnetic Activity on Measurements of Morning and Evening Asymmetry of Planetary Terminator - N. Kostogryz; A. I. Shapiro; L. Carone; L. Gizon; Ch. Helling; S. Kiefer; S. Mercier; S. Seager; S. K. Solanki; Y. Unruh; J. de Wit; V. Witzke (The Astrophysical Journal Letters)
Differences in the ingress and egress shapes of transit light curves can indicate morning–evening temperature contrasts on transiting planets. Here, we pinpoint an alternative mechanism that can introduce asymmetries in transit light curves, potentially affecting the accurate determination of morning–evening differences. Small-scale magnetic field concentrations on the surfaces of the host star affect the visibility of stellar limb regions, making them brighter relative to the nonmagnetic case. A difference in magnetization between the star’s western and eastern limbs can thus create an asymmetry in limb brightness and, consequently, an asymmetry between transit ingress and egress. We model the limb darkening and stellar limb asymmetry in solar-like stars using the 3D radiative magnetohydrodynamics (MHD) code Max-Planck-Institute für Sonnensystemforshung (MPS)/University of Chicago Radiative MHD (MURaM) to simulate magnetized stellar atmospheres and the MPS-ATLAS code to synthesize spectra using a ray-by-ray approach. Our results show that ingress–egress depth differences can reach up to 600 ppm for a 10,000 ppm transit at 0.6 μ m, depending on the magnetization of the stellar limbs, significantly interfering with planetary signals. Observations of the Sun show that such concentrations are often not accompanied by spots and do not manifest in photometric variability, indicating that even photometrically quiet stars can produce such asymmetries. However, planetary and stellar asymmetries exhibit distinct wavelength dependencies, which we propose to leverage for disentangling them.